2020
DOI: 10.3390/ijerph17072322
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Health Injuries by Job Characteristics and Working Environment among Street Cleaners in South Korea

Abstract: In 2018, 1822 incidents relating to death or injury occurred among street cleaners in South Korea. However, South Korea currently lacks comprehensive studies on related injuries based on street cleaners’ job characteristics and environments in the country. This study analyzed injuries according to the job characteristics and environment through a survey of 150 Korean street cleaners working in the Seoul and Gyeonggi-do areas. This study assessed three category measures—demographic, job characteristics, and env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
2
3
0
Order By: Relevance
“…These findings corroborate the results of previous studies. These findings corroborate with the results of studies conducted in Nigeria [25], India [26], Vietnam [27], Thailand [28], Korea [7], and Iran [29] with the observed prevalence of 78.2%, 72%, 74.4%, 88%, 69.4%, and 93% respectively. In contrast, a lower prevalence was observed in the studies conducted in Malaysia (54.5%), Egypt (60.8%), Brazil (60%), Australia (58.1%), Mekelle, Ethiopia (53.28%), and India (Chandigarh 56.8, Himachal Pradesh 58.9 [30][31][32][33][34][35][36].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These findings corroborate the results of previous studies. These findings corroborate with the results of studies conducted in Nigeria [25], India [26], Vietnam [27], Thailand [28], Korea [7], and Iran [29] with the observed prevalence of 78.2%, 72%, 74.4%, 88%, 69.4%, and 93% respectively. In contrast, a lower prevalence was observed in the studies conducted in Malaysia (54.5%), Egypt (60.8%), Brazil (60%), Australia (58.1%), Mekelle, Ethiopia (53.28%), and India (Chandigarh 56.8, Himachal Pradesh 58.9 [30][31][32][33][34][35][36].…”
Section: Discussionsupporting
confidence: 91%
“…Numerous literature has reported the occupational exposure of street cleaners to pollutants or hazardous materials and the development of diseases like; asthma, chronic respiratory diseases, eye irritations, skin conditions, stress, and hypertension [3][4][5][6][7]. Musculoskeletal disorders (MSDs) are the most common non-fatal and very disabling health problem among street cleaners.…”
Section: Introductionmentioning
confidence: 99%
“…This study found injury is less likely to occur in female as compared to male. This study is supported by a study done on South Korea (30) and Tanzania (31). This is attributed to the job category of respondents as more women were involved in street sweeping.…”
Section: Discussionsupporting
confidence: 57%
“…Most of accidents in waste management setting are related to the implementation of safety measures (16,26,27), working condition (2,22,28), environmental factors (29,30), personal factor (8,30,31), organizational factor (29). In solid waste workers, accident hazards originate from a variety of causes.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to these problems, the protection of workers from occupational hazards depends on the availability and proper utilization of protective equipment, which in low-and middle-income countries is in short supply with very limited monitoring of their utilization (7,12). Evidence also suggests that long working hours, working environments, and behavioral and technical factors adversely affect the health and wellbeing of workers (9,(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%